Effectiveness of UK provider financial incentives on quality of care: a systematic review - Mandavia, Rishi; Mehta, Nishchay; Schilder, Anne; Mossialos, Elias (British journal of general practice, 2017)
Provider financial incentives are being increasingly adopted to help improve standards of care while promoting efficiency. To review the UK evidence on whether provider financial incentives are an effective way of improving the quality of health care. Systematic review of UK evidence, undertaken in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. MEDLINE and Embase databases were searched in August 2016. Original articles that assessed the relationship between UK provider financial incentives and a quantitative measure of quality of health care were included. Studies showing improvement for all measures of quality of care were defined as 'positive', those that were 'intermediate' showed improvement in some measures, and those classified as 'negative' showed a worsening of measures. Studies showing no effect were documented as such. Quality was assessed using the Downs and Black quality checklist. Of the 232 published articles identified by the systematic search, 28 were included. Of these, nine reported positive effects of incentives on quality of care, 16 reported intermediate effects, two reported no effect, and one reported a negative effect. Quality assessment scores for included articles ranged from 15 to 19, out of a maximum of 22 points. The effects of UK provider financial incentives on healthcare quality are unclear. Owing to this uncertainty and their significant costs, use of them may be counterproductive to their goal of improving healthcare quality and efficiency. UK policymakers should be cautious when implementing these incentives - if used, they should be subject to careful long-term monitoring and evaluation. Further research is needed to assess whether provider financial incentives represent a cost-effective intervention to improve the quality of care delivered in the UK.